Sex, gender, and sexuality the new basics : an anthology - Ferber, Abby L. 1966-.; Holcomb, Kimberly; Wentling, Tre. (New York Oxford University Press, 2013)
"Pushing the boundaries of traditional sex, gender, and sexuality theories, the second edition of this edited volume brings together classic and cutting-edge works that engage, challenge, and excite. The directed reading questions before each article provides students and faculty with a roadmap, as well as the foundations to lively in-class discussions. The front-and-center list of Key Terms will prove indispensable. This fantastic resource brings together sex, gender, and sexuality through the prism of race, ethnicity, religion, ability, age, and class."--pub. desc.
26. Simone Weil Davis: "Loose Lips Sink Ships" -- 27. Eithne Luibhold: "Entry Denied: Controlling Sexuality at the Border" -- 28. Melanie Heath: "State of Our Unions: Marriage Promotion and the Contested Power of Heterosexuality" -- 29. Lionel Cantu, Jr.: "The Sexuality of Migration: Border Crossings and Mexican Immigrant Men" -- 30. Kamala Kempadoo: "Women of Color and the Global Sex Trade Transnational Feminist Perspectives" -- 31. Andrea Smith: "Rape and War against Native Women" -- 32. Barbara Perry: "Doing Gender and Doing Gender Inappropriately: Violence Against Women, Gay Men, and Lesbians" -- Part Four: (Re)Envisioning Community and Social Change -- Ntozake Shange: Poem: "With No Immediate Cause" -- 33. Tressa Anolin Navalta: "One in Front of the Other" -- 34. Nova Gutierrez: "Visions of Community for GLBT Youth: Resisting Fragmentation, Living Whole: Four Female Transgender Students of Color Speak About School" -- 35. Kate Woolfe: "It's Not What You Wear: Fashioning a Queer Identity" -- 36. Cindy Solomon: "Androgyny and Faith" -- 37. Cathy J. Cohen: "Contested Membership: Black Gay Identities and the Politics of AIDS" -- 38. George Chauncey: "'What Gay Studies Taught the Court': The Historians' Amicus Brief in Lawrence v. Texas" -- 39. Martin Rochlin: "Heterosexism in Research: The Heterosexual Questionnaire" -- 40. Avy Skolnik with The Colorado Anti-Violence Program (CAVP): "Privileges Held by Non-Trans People" -- 41. Judith Lorber: "A World Without Gender: Making the Revolution" -- 42. Leslie Feinberg: "We Are All Works in Progress".
UCWS-2014-G-1990 donated by Syracuse University Sociology Department
Keywords: Sex; Sex role; Gender identity